Impaired dendritic cell differentiation of CD16-positive monocytes in tuberculosis: role of p38 MAPK - Balboa, Luciana (2013)
Tuberculosis (TB) is one of the world´s most pernicious diseases mainly due to immune evasion strategies displayed by its causative agent Mycobacterium tuberculosis (Mtb). Blood monocytes (Mos) represent an important source of DCs during chronic infections; consequently, the alteration of their differentiation constitutes an escape mechanism leading to mycobacterial persistence. We evaluated whether the CD16+/CD16− Mo ratio could be associated with the impaired Mo differentiation into DCs found in TB patients. The phenotype and ability to stimulate Mtb-specific memory clones DCs from isolated Mo subsets were assessed. We found that CD16− Mos differentiated into CD1a+DC-SIGNhigh cells achieving an efficient recall response, while CD16+ Mos differentiated into a CD1a−DC-SIGNlow population characterized by a poor mycobacterial Ag-presenting capacity. The high and sustained phosphorylated p38 expression observed in CD16+ Mos was involved in the altered DC profile given that its blockage restored DC phenotype and its activation impaired CD16− Mo differentiation. Furthermore, depletion of CD16+ Mos indeed improved the differentiation of Mos from TB patients toward CD1a+DC-SIGNhigh DCs. Therefore, Mos from TB patients are less prone to differentiate into DCs due to their increased proportion of CD16+ Mos, suggesting that during Mtb infection Mo subsets may have different fates after entering the lungs.